1996
DOI: 10.1038/383099a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of CBP/P300 in nuclear receptor signalling

Abstract: The nuclear receptor superfamily includes receptors for steroids, retinoids, thyroid hormone and vitamin D, as well as many related proteins. An important feature of the action of the lipophilic hormones and vitamins is that the maintenance of homeostatic function requires both intrinsic positive and negative regulation. Here we provide in vitro and in vivo evidence that identifies the CREB-binding protein (CBP) and its homologue P300 (refs 6,7) as cofactors mediating nuclear-receptor-activated gene transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
555
2
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 879 publications
(589 citation statements)
references
References 26 publications
25
555
2
7
Order By: Relevance
“…One group of HATs, p300 and CREB-binding protein (CBP), are global coactivators of a variety of transcription factors involved in cell proliferation and differentiation [1821]. Nonetheless, genetic studies in mice and embryonic stem (ES) cells have clearly shown that the intrinsic HAT activity of p300, but not CBP, is specifically required for skeletal myogenesis and MyoD gene expression [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…One group of HATs, p300 and CREB-binding protein (CBP), are global coactivators of a variety of transcription factors involved in cell proliferation and differentiation [1821]. Nonetheless, genetic studies in mice and embryonic stem (ES) cells have clearly shown that the intrinsic HAT activity of p300, but not CBP, is specifically required for skeletal myogenesis and MyoD gene expression [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…They have a recognized function as transcriptional coactivators for diverse families of transcription factors, including the nuclear steroid receptors (Chakravarti et al, 1996;Hanstein et al, 1996;Kamei et al, 1996;Yao et al, 1996), and bHLH Mutoh et al, 1998;Qiu et al, 1998;Sartorelli et al, 1997;Yuan et al, 1996), leucine zipper (Bannister and Kouzarides, 1995;Bannister et al, 1995;Chrivia et al, 1993;Mink et al, 1997), and zinc ®nger (Blobel et al, 1998;Lee et al, 1995) proteins. Acting as transcriptional adaptors, they link sequence-speci®c DNA-binding proteins to components of the basal transcriptional machinery (Abraham et al, 1993;Kee et al, 1996;Nakajima et al, 1997) and to proteins with histone acetyltransferase activity (Yang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of inhibition of PMLRARa's e ect on Fos activity by ATRA is currently unknown. It recently has been shown that ligand-activated steroid hormone receptors including RARa can interact directly with CBP through their ligand-binding/dimerization domain and inhibit the AP-1 activity possibly by competing for the limited amount of CBP in the cell (Chakravarti et al, 1996;Kamei et al, 1996). This is evident for the e ect of RARa on Fos activity in the presence of retinoic acid (compare lanes 5 and 10 in Figure 2).…”
Section: Discussionmentioning
confidence: 90%
“…These alterations are mediated by an array of factors such as ligand-activated steroid hormone receptors such as the glucocorticoid receptor and retinoic acid receptor (RAR), which function as regulators of AP-1 transcription (for reviews see Pfahl, 1993;Teurich and Angel, 1995). These ligand-activated steroid hormone receptors have recently been shown to interact speci®cally with the c-AMP response element binding protein (CREB) binding protein (CBP) (Chakravarti et al, 1996;Kamei et al, 1996). Because CBP interacts with c-Fos and c-Jun (major components of AP-1) and serves as their coactivator , it has been hypothesized that inhibition of AP-1 transcription by ligand-activated steroid hormone receptors is caused by competition for limited quantities of CBP in the cell (Kamei et al, 1996).…”
Section: Introductionmentioning
confidence: 99%